2009
DOI: 10.1007/s00299-009-0713-3
|View full text |Cite
|
Sign up to set email alerts
|

Salicylic acid activates artemisinin biosynthesis in Artemisia annua L.

Abstract: This paper provides evidence that salicylic acid (SA) can activate artemisinin biosynthesis in Artemisia annua L. Exogenous application of SA to A. annua leaves was followed by a burst of reactive oxygen species (ROS) and the conversion of dihydroartemisinic acid into artemisinin. In the 24 h after application, SA application led to a gradual increase in the expression of the 3-hydroxy-3-methylglutaryl coenzyme A reductase (HMGR) gene and a temporary peak in the expression of the amorpha-4,11-diene synthase (A… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

10
94
0
1

Year Published

2011
2011
2021
2021

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 146 publications
(105 citation statements)
references
References 48 publications
10
94
0
1
Order By: Relevance
“…The expression pattern of the SQS gene Elicitors induce genes involved in the biosynthetic pathway of secondary metabolites through their specific motifs in the promoter region. Salicylic acid and methyl jasmonate cause an increase in artemisinin production in A. annua through 2 TGACG motifs in the DBR2 gene promoter (Pu et al, 2009). In the DBR2 gene promoter there is a TGA box with a TGACGT/AA sequence for responding to auxin, a GARE element with a TAACAAA/G sequence for responding to gibberellins, and a Wun motif with a TCATTTCGAA sequence for responding to wounding.…”
Section: Expression Of 2 Main Genes In the Artemisinin Biosynthesis Pmentioning
confidence: 99%
“…The expression pattern of the SQS gene Elicitors induce genes involved in the biosynthetic pathway of secondary metabolites through their specific motifs in the promoter region. Salicylic acid and methyl jasmonate cause an increase in artemisinin production in A. annua through 2 TGACG motifs in the DBR2 gene promoter (Pu et al, 2009). In the DBR2 gene promoter there is a TGA box with a TGACGT/AA sequence for responding to auxin, a GARE element with a TAACAAA/G sequence for responding to gibberellins, and a Wun motif with a TCATTTCGAA sequence for responding to wounding.…”
Section: Expression Of 2 Main Genes In the Artemisinin Biosynthesis Pmentioning
confidence: 99%
“…2 and 3). Strangely, the effect of SA treatment is quite limited compared to a reported 50% promotion of the artemisinin concentration compared to controls after 10 mM SA treatment [14]. The effect of COS on large A. annua plants has not previously been reported in literature.…”
Section: Resultsmentioning
confidence: 73%
“…But most of these experiments were conducted on suspension or hairy root culture of A. annua and not on large growing plants as in the present study. Published results showed that ADS expression could be up-regulated by SA and methyl jasmonate (MJ), but with no response to DMSO; CPR could be up-regulated by ABA and miconazole, but showed no response to SA and MJ; CYP could be up-regulated by low concentrations of MJ (22 M), and DMSO, but showed no response to high concentration of MJ (100 M), SA and miconazole [10,[13][14][15][16]. The responses in expression of these three genes regulated by SA in our experiments were in agreement with published reports [13,14].…”
Section: Resultsmentioning
confidence: 94%
“…Compared with controls, 1.0 mmol/L SA could increase the content of artemisinic acid, artemisinin, and dihydroartemisinic acid (Pu et al, 2009;Aftab et al, 2010;Guo et al, 2010). In addition, the artemisinin content of cell suspensions of A. annua treated with 20-50 mg/L (140-360 mmol/L) SA increased significantly, and the highest content was nearly 6-fold higher than that of controls (Baldi and Dixit, 2008).…”
Section: Introductionmentioning
confidence: 79%